Sex and the clock: Exploring sex differences in chronotype and circadian behavior among healthy older adults - Natalie S. Pandher; Leslie Yack; Esther Li; Quentin Coppola; Kaitlin B. Cassaletto; Lea T. Grinberg; Thomas C. Neylan; Joel H. Kramer; Christine M. Walsh (PLoS ONE, 2026)
This study aimed to compare subjective and objective circadian measures with a focus on sex differences and cognition in healthy older adults. A total of 126 participants (aged 65–90 years) completed the Horne & Ostberg Morning-Eveningness Questionnaire (MEQ) and the Circadian Type Inventory (CTI) to assess their morning-evening preference and four circadian traits: rigidity vs flexibility (CTI-FR) and languidity vs vigor (CTI-LV). These self-report measures were compared to actigraphy data from a sub-cohort of 63 individuals who wore wrist actigraphs for 24 hours a day over a 7-day period. Results showed that cognitively healthy older adults tend towards rigidity and vigor (on the CTI) and morningness (on the MEQ). Overall, the languid vs vigorous types and flexible vs rigid types displayed differences in MEQ scores. Sex moderated the association between the CTI-LV and MEQ with a steeper association in males than females (p = 0.012). Actigraphy data showed that males had less stable (interdaily stability, IS, p = 0.03) and more fragmented (interdaily variability, IV, p = 0.001) circadian rhythms than older females. Subjective MEQ scores were strongly predictive of acrophase time (p = 0.009) in males but not females. Using information processing speed (IPS) as a marker of cognitive function, we found that greater circadian rhythm fragmentation (IV) was linked to slower verbal IPS (p = 0.004) in males. Morning preference on the MEQ predicted faster spatial IPS in the overall sample (p < 0.001). These findings provide preliminary evidence of the relationship between subjective sleep preferences and objective circadian data in cognitively healthy older adults with notable sex differences in these relationships.